2018
DOI: 10.15654/tpk-170713
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich der Effizienz von Polyhexanid-Biguanid, Argon-Kaltplasma und Kochsalzlavage zur Dekontamination von Bisswunden beim Hund

Abstract: Zusammenfassung Ziel der Studie war, die Keimbelastung sowie die klinische Effizienz von Polyhexanid, Argon-Kaltplasma und Kochsalzlösung zur Reduktion der Bioburden bei Hundebissverletzungen zu überprüfen. Material und Methoden: In die Studie eingeschlossen wurden Hunde mit Bissverletzungen, die durch ein chirurgisches Debridement mit anschließender Wundbehandlung durch Lavage mit Polyhexanid-Biguanid (A), Therapie mit kaltem Argonplasma (B) oder Lavage mit physiologischer Kochsalzlösung (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We think that this effect represents the most important clinical limitation. If the results of the study by Winter et al (2018) [36] are interpreted under the light of our current findings, we think that the usage of bigger devices, which allow appropriate treatment time under clinical conditions, would most likely improve performance in vivo.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We think that this effect represents the most important clinical limitation. If the results of the study by Winter et al (2018) [36] are interpreted under the light of our current findings, we think that the usage of bigger devices, which allow appropriate treatment time under clinical conditions, would most likely improve performance in vivo.…”
Section: Discussionmentioning
confidence: 71%
“…However, the first study evaluating its effect in bite wounds in dogs did not find any decontaminating effect in vivo at all [36]. Based on the beneficial results in experimental and human applications, this finding seems odd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some differences were noted between the strains, dependent on bacterial growth phase and treatment length. The author's previous similar study [67] revealed that the overall CAP decontamination effect was lower than both polyhexanide-biguanide and saline lavages. These differences, however, were not statistically significant and the employed disinfectant did not affect the overall healing course.…”
Section: Use Of Cold Plasma For Treatment Of Chronic and Acute Woundsmentioning
confidence: 95%
“…In this study, treatment, certain differences between the species were found. In a relevant experiment conducted by the researcher, it was reported that CAP had lesser total disinfection effectiveness than saline lavages and polyhexanide-biguanide (111). Although there were differences, they were not statistically relevant, and the disinfectant used did not affect how quickly the wounds healed.…”
Section: Sciences Of Pharmacymentioning
confidence: 99%